The EU budget – how much scope for institutional reform? - Henrik Enderlein; Johannes Lindner; Oscar Calvo-Gonzalez; Raymond Ritter (European Central Bank (ECB), 2005)
This paper reviews current discussions on reforming the European Union (EU) budgetary procedure and assesses the main reform proposals that have been suggested thus far. It argues that prospects for reforms are presently hampered by the complex interplay between supranational and intergovernmental decision modes and the requirement of any budgetary procedure to strike a balance between efficiency and legitimacy. The paper reviews the main criticisms of the present budgetary procedure and the related reform proposals, which are assessed on the basis of relevant theoretical literature as well as brief comparisons with the federal budget of the United States. The paper argues that the current EU budgetary procedure maximises efficiency and legitimacy, given the present state of political integration in the EU. Significant modifications to the budgetary procedure would depart from that equilibrium.
Keywords: 330; Öffentlicher Haushalt; Haushaltsrecht; Finanzreform; EU-Staaten